2020
DOI: 10.1021/acsaem.0c00476
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Pseudocapacitance: A Way to Harness Charge Storage of Crystalline RuO2

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…These experiments provide clear-cut evidence for the transformation of RuO 2 to hydrous RuO 2 and then to metallic Ru. Upon cathodic polarization in the HER potential region (down to −100 mV SHE ), first the layer spacing of RuO 2 (110) increases (SXRD, l-scan Figure b), a process that is reconciled with proton insertion into the RuO 2 lattice and that may be interesting for charge storage in crystalline RuO 2 . However, both the octahedral coordination of Ru and the connectivity of the Ru–O 6 octahedrons (rutile structure) are still preserved.…”
Section: Critical Discussion Of Selected Model Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments provide clear-cut evidence for the transformation of RuO 2 to hydrous RuO 2 and then to metallic Ru. Upon cathodic polarization in the HER potential region (down to −100 mV SHE ), first the layer spacing of RuO 2 (110) increases (SXRD, l-scan Figure b), a process that is reconciled with proton insertion into the RuO 2 lattice and that may be interesting for charge storage in crystalline RuO 2 . However, both the octahedral coordination of Ru and the connectivity of the Ru–O 6 octahedrons (rutile structure) are still preserved.…”
Section: Critical Discussion Of Selected Model Studiesmentioning
confidence: 99%
“…Upon cathodic polarization in the HER potential region (down to −100 mV SHE ), first the layer spacing of RuO 2 (110) increases (SXRD, l-scan Figure 9b), a process that is reconciled with proton insertion into the RuO 2 lattice and that may be interesting for charge storage in crystalline RuO 2 . 203 However, both the octahedral coordination of Ru and the connectivity of the Ru− O 6 octahedrons (rutile structure) are still preserved. A further increase in the cathodic potential steadily destroys the crystallinity of the RuO 2 (110) layer (Figure 9a,b), likely via the formation of OH and water from lattice O, thereby breaking the connectivity among the Ru−O 6 octahedrons in the rutile RuO 2 structure.…”
Section: Critical Discussion Of Selected Model Studiesmentioning
confidence: 99%
“…The above results proved that the pseudocapacitance of RuO 2 came from the surface redox reaction, not the bulk reaction of RuO 2 . In order to better understand the charge storage mechanism of RuO 2 in acidic media, more and more researchers have begun to use theoretical calculation methods to analyze the thermodynamic and kinetic behavior of RuO 2 on the atomic scale [ 46 49 ]. The results of first-principles density-functional theory (DFT) showed that the intercalation of protons would lead to the formation of O–H covalent bonds and the formation of an electronic delocalization state for only 0.3 electrons transferring to the Ru atom center.…”
Section: Electrochemical Proton Storage Materials and Mechanismsmentioning
confidence: 99%
“…Numerous studies, however, serve to demonstrate this pseudocapacitive behavior (Figure S1, Supporting Information). [ 2,4,11–44 ] This thus leads one to consider the possible reasons for a redox reaction, which is essentially a Faradaic occurrence, deviating so far from the ideal peak response (as illustrated in Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%